What drives trade in services? Lessons from the Nordics - Hildegunn Kyvik Nordås (Örebro University School of Business, 2017)
The contribution of this paper to the literature is to make an empirical assessment of the relative importance of non-actionable institutional and cultural factors and actionable policy measures for services market integration, using the Nordic countries as a case study. It finds that intra-Nordic trade in services is about 2.5 times larger than predicted from the gravity model. This may not be surprising since the Nordics are perceived as a cluster of similar countries, but a detailed analysis of the Nordics' policy framework, trade agreements, institutional and cultural factors concludes that these cannot explain the intra-Nordic bias. An unexplained "Nordicness" factor of this magnitude indicates that integration of services markets may rely on deeper institutional and cultural factors that do not readily lend themselves to trade negotiations. Conversely, trade agreements may yield the largest benefits among countries that share common cultural and institutional features.
Keywords: F13; F14; 330; Services trade; trade barriers; regulation